Problematyka dydaktyki polonistycznej w dorobku twórczym profesor Stefanii Skwarczyńsklej = Problems of didactics of Polish Studies in creative achievements of professor S. Skwarczyńska - Bogołębska, Barbara (Zielona Góra: Wyższa Szkoła Pedagogiczna)
The article concerns the little known, and untouched by biographers, period of time in professer Skwarczyńska's didactic work on secondary education before 1939. She wrote same valuable dissertation papers devoted to didactics of Polish Studies and educational themes then. The article also deals with professer Skwarczyńska's social activity among Polonists in Łódź before the War.
Keywords: Skwarczyńska, Stefania (1902-1988); dydaktyka literatury